PERSEPSIRETAILERMODERNTERHADAPSALESPOMOTIONGIRLSARIHUSADA(StudiKasuspadaPTTigaraksaSatriaJambiDistributorSariHusada) MODERNRETAILERPERCEPTIONSONSARIHUSAD’SSALESPROMOTIONGIRL(CaseStudyatPTTigaraksaSatriaasSariHusada’sDistributorJambi) - Johannes .; Erida .; Hanafi . (DIGEST MARKETING, 2012)
PrincipalandDistributorofproductsrealizethatthetrendofconsumersshoppingatmodernretailersisincreasingsignificantly.Therefore,theyhavetomanageitinordertogetmarketgrowingandovercomingcompetition.OneofthestrategiestocompeteisuseSalesPersonGirl(SPG).ThisstudypurposeistodeterminethemodernretailerperceptionsonSPG’scompetence.Thestudywasconductedon13modernretailerswhichareregularlyvisitedby7SPGofSariHusada.Theresearchmethodmainlyusedqualitativemethod.Toenrichthedata,quantitativemethodusestomeasureperceivedvalueandtodescribethepartnershipstrategyincoordinationwithSPG.Keywords:principal,modernretailers,retailmanagement,modernstoreperception.